Why we use more materials. (13th June 2017) - Gutowski, Timothy; Cooper, Daniel; Sahni, Sahil
Abstract : In this paper, we review the drivers for the high levels of material use in society, investigating both historical and current trends. We present recent national and global data by different material categories and accounting schemes, showing the correlations between materials use and different measures of human well-being. We also present a development narrative to accompany these observed trends, focusing on the strong role materials have played in economic development by industrialization and in the consumer economy. Finally, we speculate on how material efficiency might alter this pattern going forward and whether it is possible to de-couple well-being from material use. This article is part of the themed issue 'Material demand reduction'.